Catholicism a very short introduction - O'Collins, Gerald 1931- (Oxford University Press, 2008)
Among the topics covered in this introduction to the largest and oldest institution in the world are the origins of the Catholic Church, how Catholicism has changed and adapted over the centuries and the challenges the Catholic Church faces in the 21st century
Keywords: Catholic Church / Doctrines / Customs and practices; Katholische Kirche; Catholic Church -- Doctrines; Catholic Church -- Customs and practices; RELIGION / Christianity / Catholic; Christentum; Katholizismus; Einführung